Serum- and HDL3-serum amyloid A and HDL3-LCAT activity are influenced by increased CVD-burden. (January 2016) - McEneny, Jane; McKavanagh, Peter; York, Edmund; Nadeem, Nida; Harbinson, Mark; Stevenson, Michael; Ball, Peter; Lusk, Lisa; Trinick, Thomas; Young, Ian S.; McKay, Gareth J.; Donnelly, Patrick M.
Abstract: Background: High density lipoproteins (HDL) protect against cardiovascular disease (CVD). However, increased serum amyloid-A (SAA) related inflammation may negate this property. This study investigated if SAA was related to CVD-burden. Methods: Subjects referred to the rapid chest pain clinic (n = 240) had atherosclerotic burden assessed by cardiac computerised tomography angiography. Subjects were classified as: no-CVD (n = 106), non-obstructive-CVD, stenosis<50% (n = 58) or moderate/significant-CVD, stenosis ≥50% (n = 76). HDL was subfractionated into HDL2 and HDL3 by rapid-ultracentrifugation. SAA-concentration was measured by ELISA and lecithin cholesterol acyltransferase (LCAT) activity measured by a fluorimetric assay. Results: We illustrated that serum-SAA and HDL3 -SAA-concentration were higher and HDL3 -LCAT-activity lower in the moderate/significant-CVD-group, compared to the no-CVD and non-obstructive-CVD-groups (percent differences: serum-SAA,  +33% & +30%: HDL3 -SAA,  +65% and +39%: HDL3 -LCAT,  −6% & −3%; p < 0.05 for all comparisons). We also identified a positive correlation between serum-SAA and HDL3 -SAA (r = 0.698; p < 0.001) and a negative correlation between HDL3 -SAA and HDL3 -LCAT-activity (r = −0.295; p = 0.003), while CVD-burden positively correlated with serum-SAA (r = 0.150; p < 0.05) and HDL3 -SAA (r = 0.252; p < 0.001) and negatively correlated with HDL3 -LCAT-activity (r = −0.182; p = 0.006). Additionally, multivariate regression analysis adjusted for age, gender, CRP and serum-SAA illustrated that HDL3 -SAA was significantly associated with modifying CVD-risk of moderate/significant CVD-risk (p < 0.05). Conclusion: This study has demonstrated increased SAA-related inflammation in subjects with moderate/significant CVD-burden, which appeared to impact on the antiatherogenic potential of HDL. We suggest that SAA may be a useful biomarker to illustrate increased CVD-burden, although this requires further investigation. Highlights: SAA-related inflammation is increased in subjects with moderate/significant CBD-burden. SAA-related inflammation impacts on the antiatherogenic potential of HDL. SAA may be a useful biomarker to illustrate increase CVD-burden.